Beethoven series, alternating Sundays beginning October 9th, [1938], 8:45 p.m., Federal Music Theatre, 254 W. 54th Street, N.Y.C. (New York, 2020)
Program for the W.P.A. Federal Music Project Beethoven concert series, October 9-December 18, 1938, in New York. Includes a reading list of books about Beethoven.